Turystyka kulturowa w okresie redefinicji podróżowania. Nowe zasoby, alternatywne formy organizacji, zarządzanie kryzysowe - Mikos von Rohrscheidt, Armin (1966- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The publication refers to the creation and management of the cultural tourism offer, taking into account the interests of its key stakeholders. Its subject is a critical analysis of selected exploitation forms of cultural resources and solving related problems, an analysis of the sources and effects of difficulties in managing selected tourism products, as well as a summary of recommendations for management activities (including remedial and corrective measures) undertaken in crisis situations, especially recently affecting global tourism. The topics of individual chapters are determined by current problems related to the organization of travel aimed at experiencing the values of living culture and confronting cultural heritage.
Keywords: turystyka kulturowa; zarządzanie w turystyce; organizacja turystyki; zarządzanie kryzysowe; cultural tourism; tourism management; tourism organization; crisis management